CHANGES IN MELATONIN CONCENTRATION DEPENDING ON THE SEVERITY OF CHRONIC CEREBRAL ISCHEMIA AND SEASONALITY - Adambayev, Z.I.; Yakubova, M.M.; Olmosov, R.Sh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Chronic cerebral ischemia (CCI) accounts for almost 2/3 of cerebrovascular diseases and causes cognitive impairment. Melatonin deficiency also causes the development of cerebral disorders due to the deterioration of cerebral circulation due to atherosclerotic damage to cerebral vessels and degenerative processes of nervous tissue. In our article, we studied the changes in melatonin concentration depending on the severity of chronic cerebral ischemia and seasonality. 80 patients with CCI were examined. The mean age of the patients was 57.8±11.4 years. Patients were divided into 3 groups depending on the stage of CCI disease and the date of collecting blood serum. It is determined that as the stage of the disease increases, the concentration of melatonin in patients decreases. The lowest concentration was in summer, and the highest concentration was determined in winter